Testing the Product Quality, Brand Ambassador, Product Design and Lifestyle against the OPPO Smartphone Purchasing Decision - Penny Sukma Nuryanti; Budi Istiyanto (International Journal of Seocology, 2020)
This research is motivated by the smartphone market which is increasing and more and more is interested in smartphone products, so that it becomes one of the backgrounds of Oppo smartphones to take part in enlivening the smartphone market. The purpose of this study was to determine the effect of product quality, brand ambassadors, product design and lifestyle on purchasing decisions for the Oppo smartphone. The research method used is quantitative research methods. The determination of the samples number are using Rao Purba formula and obtained a sample of 96 respondents. The results show that there is a positive and significant influence between product quality, brand ambassadors, product design and lifestyle on purchasing decisions for Oppo brand smartphones.